Epidemiology of high blood pressure among the Kaingang people on the Xapecó Indigenous Land in Santa Catarina State, Brazil, 2013 - Deise Bresan; João Luiz Bastos; Maurício Soares Leite (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
This cross-sectional study describes the prevalence of high blood pressure (HBP; measured at one setting, and suggestive of a clinical diagnosis of arterial hypertension) and mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) and their associations with socio-demographic and anthropometric variables among 355 Kaingang adults (≥ 20 years) on the Xapecó Indigenous Land in Brazil. Weight, height, waist circumference (WC), SBP, and DBP were measured and socio-demographic data were collected. Prevalence of HBP was 53.2% (95%CI: 45.3; 61.1) in men and 40.7% (95%CI: 33.8; 47.6) in women. In women, age and WC were directly associated with HBP; age was associated with SBP and schooling with DBP. In men, HBP was statistically associated with high body mass index (BMI) and tile floor in the home (as a socioeconomic proxy); BMI and WC were associated with SBP; BMI and WC were associated with DBP. The study highlights the need for measures to control risk factors for HBP, especially due to its relevance for cardiovascular diseases and their consequences.